Change management decisions in the information age - Davidavičienė, Vida (Journal of Business Economics and Management, 2008)
The work under new conditions of ICT development has not only advantages, but also causes certain challenges and new conflicts within an organization. There is a direct link between the development of ICT and business management theories. Inadequacy of models applied in change management and current market requirements can determine the decrease of competitive ability for the business organizations in the ICT caused business environment, what can cause loss of potential markets. The relations between ICT and business in the development processes and trends must be determined in order to avoid the gaps in business management methods in the future. While the schemes for evaluation and selection of alternative decisions are given much attention in the strategic management literature, the attention given to the specific implementation and the practical application of change management decisions methods is not sufficient. These circumstances frame the topicality of this subject.First published online: 14 Oct 2010